Histopathology, Isolation and Molecular Detection of Pasturella multocida from Sheep in Gadag Region of Karnataka, India - Chandrashekar KM; Ballari, Shashidhar; Sanjeev Kumar M; Angadi, Akshata S.; Chawhan, Pradeep; Shivaraj B M (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Bacterial pneumonia is the most common respiratory problem in small ruminants. The heart blood and lung tissue samples from two dead sheep suffering from pneumonia at the age of six month were subjected for histopathology, bacterial isolation & identification and antibiogram. Acute fibrinous bronchopneumonia was observed at necropsy and histopatholgy. The isolates were identified as P. multocida based on cultural and biochemical properties, and additionally confirmed by species-specific PCR amplification of KMT1 (Multocida toxin hydrolase gene) gene with the amplicon of 460 bp. The antibiogram showed susceptibility to chloramphenicol, β-lactams, quinolones, fluoroquinolones and aminoglycosides. In this study, the occurrence of ovine pasteurellosis caused by P. multocida with acute fibrinous bronchopneumonia was recorded.